2022
DOI: 10.1039/d1cy02090k
|View full text |Cite
|
Sign up to set email alerts
|

Insight into the performance of different Pt/KL catalysts for n-alkane (C6–C8) aromatization: catalytic role of zeolite channels

Abstract: Zeolite channel architecture was vital to catalytic activity and products distribution during the naphtha reforming, which could be effectively utilized by designing the locations of active sites. Herein, uniformly dispersed...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 45 publications
(95 reference statements)
0
13
0
Order By: Relevance
“…The product analysis as a function of conversion revealed that EB and X are produced as primary products by direct closure of the six-membered ring, then their hydrogenolysis inside the channels of the zeolite produces benzene and toluene. In another case, the Pt/KL catalyst was prepared using the atomic layer deposition (ALD) , method to introduce Pt nanoparticles deep within the channels of the zeolite. The exposure time to the Pt precursor considerably influenced the diffusion depth within the KL-zeolite, as shown in Figure .…”
Section: Aromatization Catalystsmentioning
confidence: 99%
“…The product analysis as a function of conversion revealed that EB and X are produced as primary products by direct closure of the six-membered ring, then their hydrogenolysis inside the channels of the zeolite produces benzene and toluene. In another case, the Pt/KL catalyst was prepared using the atomic layer deposition (ALD) , method to introduce Pt nanoparticles deep within the channels of the zeolite. The exposure time to the Pt precursor considerably influenced the diffusion depth within the KL-zeolite, as shown in Figure .…”
Section: Aromatization Catalystsmentioning
confidence: 99%
“…9,10 On the other hand, the aromatization of long-chain alkanes (C 7 -C 9 ), the main components of naphtha, can be operated under relatively mild conditions and it gives higher aromatic selectivity (>60%). 11,12 Since long-chain alkanes have a larger molecular size, their adsorption and diffusion suffer from strong limitation over medium-pore ZSM-5, thus resulting in fast deactivation. Meanwhile, although Brønsted acid sites are necessary for the aromatization of olefins generated from alkane dehydrogenation, their amount and strength should be finely regulated to avoid over-cracking reaction.…”
Section: Introductionmentioning
confidence: 99%
“…15–18 The selectivity for aromatics decreases to less than 60% with n -octane as feed, and the principal products are the secondary hydrogenolysis species of the desired C 8 aromatics. 19,20 In addition, it shows poor stability during the aromatization of larger-sized alkanes, being rapidly deactivated at the initial reaction stage. 18,21 Combined with our previous work and the literature, this is closely related to the topological structure of KL zeolite, leading to non-negligible diffusion-limitation with larger-sized alkanes as feed.…”
Section: Introductionmentioning
confidence: 99%
“…18,21 Combined with our previous work and the literature, this is closely related to the topological structure of KL zeolite, leading to non-negligible diffusion-limitation with larger-sized alkanes as feed. 20,21 Therefore, a zeolite with another topological structure requires further discussion, to construct a suitable catalytic system for the dehydrocyclization of larger-sized alkanes.…”
Section: Introductionmentioning
confidence: 99%